Association between Diffusion Tensor Imaging, inflammation and immunological alterations in unipolar and bipolar depression: A review. (December 2022) - Aronica, Rosario; Enrico, Paolo; Squarcina, Letizia; Brambilla, Paolo; Delvecchio, Giuseppe
Abstract: Major Depressive Disorder (MDD) and Bipolar Disorder Depression (BDD) are common psychiatric illnesses characterized by structural and functional brain alterations and signs of neuroinflammation. In line with the neuroinflammatory pathogenesis of depressive syndromes, recent studies have demonstrated how white matter (WM) microstructural impairments detected by Diffusion Tensor Imaging, are correlated to peripheral immunomarkers in depressed patients. In this context, we performed a comprehensive systematic search on PubMed, Medline and Scopus of the original studies published till June 2022, exploring the association between immunomarkers and WM alteration patterns in patients affected by MDD or BDD. Overall, the studies included in this review showed a consistent association between blood proinflammatory and counter-regulatory immunomarkers, including regulatory T cells and natural killer cells markers, as well as measures of demyelination and dysmyelination in both MDD and BDD patients. These pathogenetic insights could outline an integrated clinical perspective to affective disorders, helping psychiatrists to develop novel biotype-to-phenotype models of depression and opening the way to tailored approaches in treatments. Highlights: Plasma BDNF levels increase in parallel to the myelin inflammatory damage indicators in MDD patients. The increase of pro-inflammatory cytokines is correlated to DT-MRI indicators of WM damage in MDD patients. The correlation between the WM damage and IL-10 supports the involvement of the counter-regulatory immunity in BDD patients. WM integrity is directly associated to Th17 and Treg levels in BDD patients. NK cells play an important role in maintaining WM integrity in BDD patients.